The Legal Basis of Information Technology Based Cofinancing Services in Indonesia - Afif Noor; Ali Maskur (Universitas Islam Negeri Walisongo Semarang, 2022)
The rapidly growing information technology-based co-financing service (LPBBTI) in Indonesia requires a forceful legal basis for the parties involved in information technology-based financial services. As a rule-of-law country, Indonesia must make the rule of law the commander in chief and guide behavior. This research seeks to find the legal basis of LPBBTI in the laws and regulations of Indonesia, which is carried out by document study and uses a statute approach. The data obtained were then analyzed qualitatively. This research did not find any legal basis for LPBBTI in the law, but there are several laws related to LPBBTI, such as the Civil Code and Law No. 11 of 2008. The legal basis for LPBBTI specifically only exists in the Financial Services Authority Regulation No. 10/POJK.05/2022 and No. 13/POJK.02/2018.Layanan Pendanaan Bersama Berbasis Teknologi Informasi (LPBBTI) yang berkembang pesat di Indonesia memerlukan landasan hukum kuat sebagai panduan para pihak yang terlibat dalam layanan keuangan berbasis teknologi informasi tersebut. Indonesia sebagai penganut negara hukum harus menjadikan hukum sebagi panglima dan pedoman dalam bertingkah laku. Penelitian ini berusaha menemukan landasan hukum LPBBTI dalam peraturan perundang-undangan di Indonesia yang dilakukan dengan studi dokumen dan menggunakan pendekatan statute. Data yang diperoleh kemudian dianalisa secara kualitatif. Penelitian ini tidak menemukan landasan hukum LPBBTI dalam undang-undang tetapi ada beberapa undang-undang yang terkait dengan LPBBTI seperti Kitab Undang-Undang Hukum Perdata dan Undang-Undang No. 11 tahun 2008. Dasar Hukum LPBBTI terdapat dalam Peraturan Otoritas Jasa Keuangan No. 10/POJK.05/2022 dan No. 13/POJK.02/2018.